DNA barcoding reveals underestimated species diversity of mantis shrimp larvae (stomatopods) in Banten Bay, Indonesia - ABINAWANTO ABINAWANTO; MARIANA D. BAYU INTAN; WISNU WARDHANA; ANOM BOWOLAKSONO (Society for Indonesian Biodiversity, 2019)
Abstract. Abinawanto, Intan MDB, Wardhana W, Bowolaksono A. 2019. DNA barcoding reveals species diversity of mantis shrimp larvae (stomatopods) from Banten Bay, Indonesia. Biodiversitas 20: 1758-1763. Larvae of stomatopods can be morphologically identified by linking between larval and adult form, but it's difficult applied in the laboratory because of requirement of condition to rearing larvae collected either from plankton, or spawning adults in the laboratory. Molecular methods are the alternative approach to gather accurate taxonomic identification. One of molecular methods is DNA barcoding based upon sequence diversity in cytochrome c oxidase subunit 1 (COI). Research on stomatopod larvae diversity and distribution at six stations in Banten Bay has been studied from October 2013 to March 2014. This study was conducted to identify the diversity of stomatopod larvae through DNA barcoding and also to examine the distribution of stomatopod larvae in Banten Bay. DNA barcoding was used to identify mantis shrimp larvae in Banten Bay, Indonesia. Partial mitochondrial COI were obtained for 37 larvae, revealing five distinct molecular operational taxonomic units (MOTUs). All MOTUs distinctively fell into Squillidea clade. Two Molecular Operational Taxonomic Units, MOTUs were successfully identified to species level (i.e. Anchisquilla fasciata), while three others remained identified to genus level (i.e. Stomatopoda spp). The intraspecific variation of COI ranged from 0% to 3.1% (Kimura 2-parameter distance), whereas interspecific divergence ranged from 5.9% to 20.4%. These results imply that COI genes are suitable for species identification of stomatopod larvae in this area, though the number of unidentified species was higher than the identified ones. This is likely because of the limited database in GenBank. In addition, the two identified species represents new records for this area, suggesting that the mantis shrimp in the area have been underestimated based on traditional biodiversity measures. We recommend to develop a taxonomically-comprehensive DNA barcoding database to improve the accuracy and feasibility of using DNA barcoding for species identification of Indonesia mantis shrimps.